Evaluation of the implementation of Indonesian language program for foreign speakers (BIPA) at Universitas Negeri Yogyakarta (UNY) - Mwakapemba, James Leonard; Satria, Mohammad Rizky; Sudiyatno, Sudiyatno; Lumenyela, Rogers Andrew (Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
This study aims to evaluate the Indonesian Language for Foreign Speakers program (BIPA) at Universitas Negeri Yogyakarta (UNY). The evaluation research employs a mixed-method approach, which includes qualitative and quantitative methods. The study was guided by using the CIPP Model (Context, Input, Process, Product) developed by Stufflebeam. Data collection in this study used interviews, documentation, and questionnaires. The data were also analyzed using descriptive quantitative statistics and an interactive model data analysis. The evaluation results indicate that in the context component, the UNY BIPA program has a suitable curriculum and learning materials aligned with the Ministry of Education and Culture, Regulation No. 70 of 2016. In the input component, the program's progress scored 23.85, which is in a very good category, and its program implementation is very successful, reaching 85.18%. This indicates successful implementation in key areas such as teacher recruitment, materials, and infrastructure. In the process component, the program's progress is in a good category, with a score of 24.41, and its overall program implementation is successful, with 76.28%, reflecting a well-run teaching and learning process with high student satisfaction. However, challenges include ineffective online learning, limited teaching materials, commitment issues, and a lack of student assessment tests. In the product component, the program's progress scored 19.61, which is in a very good category, and its overall program implementation is successful, with 81.74%, indicating very successful achievement of program objectives. Nonetheless, it does not fully support students' academic needs during lectures